PENGARUH HARGA SAHAM DAN FREKUENSI PERDAGANGAN SAHAM TERHADAP BID-ASK SPREAD (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG MELAKUKAN STOCK SPLIT DI BURSA EFEK INDONESIA SELAMA PERIODE 2009-2014 - Patoni, Ahmad; Lasmana, Andy (Fakultas Ekonomi Universitas Djuanda, 2015)
The purpose of this study was to examine the effect of stock prices and trading frequency of the bid-ask spread on a manufacturing company doing stock split. The population in this study is a manufacturing company doing stock split which consists of 28 companies. Determination of the study sample consists of 24 companies conducted using purposive sampling method.As for hypothesis testing and research instruments using multiple regression analysis SPSS 20.0. Results of this study prove that the stock price does not affect the bid-ask spread. While the frequency stock trading affect the bid-ask spread.